2017
DOI: 10.1016/j.jallcom.2017.03.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the impact energy on the chemical homogeneity of a (Ti,Ta,Nb)(C,N) solid solution obtained via a mechanically induced self-sustaining reaction

Abstract: A titanium-tantalum-niobium carbonitride solid solution, (Ti,Ta,Nb)(C,N), was synthesised in a planetary mill via a mechanochemical process that involves a mechanically induced self-sustaining reaction (MSR) from stoichiometric Ti/Ta/Nb/C mixtures that are milled under a nitrogen atmosphere. The influence of the spinning rate of the planetary mill, which determines the impact energy of the milling process, on the ignition time (t ig) of the MSR process as well as the chemical homogeneity of the final product w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Avoidance of heavy transition elements in Ti(C,N)-FeNi cermets has also led to CSS materials [143,151,199]. Last, through mechanochemical processing (MCP), (Ti,Mo)C and (Ti,Ta,Nb)(C,N)-based CSS cermets were synthetised from elemental powders [140,196,200,201]. Microstructural features -more specifically grain size and binder content -govern the properties and applications of the manufactured hard materials.…”
Section: Influence Of the Microstructurementioning
confidence: 99%
“…Avoidance of heavy transition elements in Ti(C,N)-FeNi cermets has also led to CSS materials [143,151,199]. Last, through mechanochemical processing (MCP), (Ti,Mo)C and (Ti,Ta,Nb)(C,N)-based CSS cermets were synthetised from elemental powders [140,196,200,201]. Microstructural features -more specifically grain size and binder content -govern the properties and applications of the manufactured hard materials.…”
Section: Influence Of the Microstructurementioning
confidence: 99%
“…Concretely, the syntheses carried out by Garcia-Garrido et al [8,9] were possible by means of MA, which has been reported to be a simple, economic, and reproducible method, in the following ways: to extend the metal solubility; to produce complete solid solutions; to refine the structure up to nanometric levels, and to synthesize new crystalline phases, such as the novel high-entropy alloys (HEAs) [16], quasi-crystalline phases, and amorphous phases, among other interesting abilities [17]. With respect to MA, it has been established that not only the rate of the reaction, but also the reaction route and the products obtained, can be highly influenced by using different milling equipment and milling conditions [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new, simple, affordable, and reproducible mechanochemical method, denoted as mechanically induced self-sustaining reaction (MSR), has been successfully applied for the synthesis of complex solid solution carbonitrides with optimal stoichiometric control [18,19] and the development of cermets based on them. The MSR method is a reactive milling process that uses the exothermic nature of the carbonitride formation to synthesize them from the mixture of transition metal elements and a carbon source (usually graphite) under a reactive N 2 atmosphere.…”
Section: Introductionmentioning
confidence: 99%